2009
DOI: 10.1080/00365520802495545
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ attitudes towards endoscopic ultrasound: A survey of four European countries

Abstract: The majority of responding clinicians use EUS but overall utilization varies considerably among different countries. There is considerable variation in EUS service availability and accessibility among countries which, together with perceived usefulness of EUS, is a major determinant of EUS utilization. A shortage of trained endosonographers and the high cost are major barriers to wider EUS use. The findings of this study might help to define policies aimed at development of EUS services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
1
17
0
7
Order By: Relevance
“…This result is consistent with those of Western surveys that have also reported that a shortage of endosonographers is the main barrier to wider use of EUS (1,2). Although the American Society for Gastrointestinal Endoscopy has published guidelines for training, credentialing, and granting privileges for EUS (23,24), this is not the case for KSGE or for many national associations of gastrointestinal endoscopy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result is consistent with those of Western surveys that have also reported that a shortage of endosonographers is the main barrier to wider use of EUS (1,2). Although the American Society for Gastrointestinal Endoscopy has published guidelines for training, credentialing, and granting privileges for EUS (23,24), this is not the case for KSGE or for many national associations of gastrointestinal endoscopy.…”
Section: Discussionsupporting
confidence: 80%
“…Reports on Western endoscopists' clinical attitudes toward EUS use for gastrointestinal malignancies have been published (1,2). However, Eastern endoscopists' clinical attitudes in this regard remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although technically easy, there is a learning curve to attain proficiency in EUS-FNA and the technology is not widely available. [15][16][17][18] Analysis of the claims data revealed that while EUS-FNA is increasingly being used, surgical biopsies are becoming less common. At present, at most major medical centers, the role of open surgical biopsies of the pancreas is relegated only to cases where multiple attempts at EUS-FNA are unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate achieved after three e-mail circulations of the questionnaire is relatively low, but not wholly unexpected for this type of survey, and is similar to the response rate achieved in a recent e-mail survey of the accessibility of endoscopic ultrasound in European countries which included the UK and Greece. The response rate to that survey was 15% for members of the British Society of Gastroenterology and 25% for members of the Hellenic Society of Gastroenterology [22].…”
Section: Discussionmentioning
confidence: 99%